Comparison of the Physiological Effect of Billroth-I and Roux-en-Y Reconstruction Following Laparoscopic Distal Gastrectomy. Issue 5 (October 2018) - Toyomasu, Yoshitaka; Ogata, Kyoichi; Suzuki, Masaki; Yanoma, Toru; Kimura, Akiharu; Kogure, Norimichi; Ohno, Tetsuro; Kamiyama, Yoichi; Mochiki, Erito; Kuwano, Hiroyuki
Abstract : Background: Laparoscopic distal gastrectomy (LDG) is a widely used minimally invasive surgery. Following LDG, Billroth-I (B-I) provides physiological reconstruction by preserving the duodenal passage but results in a high incidence of reflux esophagitis that decreases postoperative quality of life. Because of this, Roux-en-Y (R-Y) reconstruction is often considered the first choice after LDG. However, very few studies have investigated differences in physiological function between B-I and R-Y after LDG. We hypothesized that B-I would outperform R-Y in clinical and physiological outcomes, including nutrition parameters. Methods: We compared hemoglobin, ferritin, serum iron, Vitamin B12, 25(OH)-Vitamin D (V-D), body weight, and gastric emptying after LDG in patients with either B-I or R-Y reconstruction. Results: The levels of hemoglobin in the B-I group were significantly higher than that in the R-Y group at all time points later than 6 months postsurgery. The ferritin levels were significantly higher in the B-I group at all time points later than 9 months postsurgery. The concentration of serum V-D in the B-I group was significantly higher than that in the R-Y group at 1 year 6 months, 1 year 9 months, and 2 years after surgery. Gastric emptying in the R-Y group was significantly slower than in the B-I group. Conclusions: Our data indicate that B-I leads to less postsurgical iron deficiency anemia and V-D deficiency compared with R-Y reconstruction. Furthermore, gastric emptying was preserved in B-I reconstruction compared with R-Y reconstruction. In conclusion, after LDG, B-I reconstruction seems to cause fewer nutritional complications than R-Y reconstruction.